2013
DOI: 10.1093/bja/aet120
|View full text |Cite
|
Sign up to set email alerts
|

Neuraxial block, death and serious cardiovascular morbidity in the POISE trial

Abstract: In patients at high risk of cardiovascular morbidity, neuraxial block was associated with an increased risk of adverse cardiovascular outcomes, which could be causal or because of residual confounding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 29 publications
2
42
3
1
Order By: Relevance
“…Uncertainty remains in part because previous studies did not differentiate between neuraxial anesthesia alone vs the combination of neuraxial and general anesthesia. 5,[8][9][10] Contrary to other research findings, a post hoc analysis of patients at high risk for cardiovascular complications in the POISE trial showed that patients who received neuraxial blockade were actually at greater risk for cardiovascular complications. 10 We therefore conducted a large population-based study to explore this Ontario who are 65 yr of age or older.…”
contrasting
confidence: 66%
See 3 more Smart Citations
“…Uncertainty remains in part because previous studies did not differentiate between neuraxial anesthesia alone vs the combination of neuraxial and general anesthesia. 5,[8][9][10] Contrary to other research findings, a post hoc analysis of patients at high risk for cardiovascular complications in the POISE trial showed that patients who received neuraxial blockade were actually at greater risk for cardiovascular complications. 10 We therefore conducted a large population-based study to explore this Ontario who are 65 yr of age or older.…”
contrasting
confidence: 66%
“…5,[8][9][10] Contrary to other research findings, a post hoc analysis of patients at high risk for cardiovascular complications in the POISE trial showed that patients who received neuraxial blockade were actually at greater risk for cardiovascular complications. 10 We therefore conducted a large population-based study to explore this Ontario who are 65 yr of age or older. The ODB database records prescription characteristics, including the drug identification number, the number of days supplied, and the date the prescription was filled.…”
contrasting
confidence: 66%
See 2 more Smart Citations
“…259 Furthermore, combination of general anaesthesia with thoracic epidural anaesthesia has been shown to statistically increase the risk of arterial hypotension. 260 …”
Section: Neuraxial Techniquesmentioning
confidence: 99%